SISTEM PENDUKUNG KEPUTUSAN DATA ALUMNI SARJANA KOMPUTER MENGGUNAKAN METODE INFERENSI MAMDANI BERBASIS MATLAB - Yustria Handika Siregar (Universitas Asahan, 2017)
Abstract - The rapid development of information technology has triggered many people to find alternative solutions to problems in the field of information system technology. As a case of a decision to choose a job, position or a particular career which is a series of consequences of decisions made by individuals at the stages of their lives in the past. The use of a support system for this decision can provide convenience to alumni in determining job choice in accordance with the ability or value of alumni data. The problem to be discussed in this study is how to choose the right job criteria using the Mamdani method. Keywords - Decision Support System, Mamdani, Alumni Data